1984
DOI: 10.1093/rheumatology/23.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Epidural Injections in the Treatment of Sciatica

Abstract: A randomized trial of lumbar epidural injections for the treatment of acute sciatic pain was carried out. All the patients had unilateral sciatica for less than six months and had never previously been treated in hospital for their backs. The treatments used were 20 ml normal saline, 80 mg Depomedrone in normal saline made up to 20 ml, 20 ml, 20 ml 0.25% bupivacaine solution and needling with a standard Touhy injection needle into the interspinous ligament but with no injection. The patients improved at about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 0 publications
0
71
0
7
Order By: Relevance
“…67,81,83 Both injections were examined in one study of high methodological and technical quality with 130 patients using four "control" groups. In this study 81 the proportion of patients with 50% or more pain relief was not significantly different among all comparison groups: 7% for transforaminal local anesthetic, 19% for transforaminal saline, 21% for intramuscular steroids, and 13% for intramuscular saline.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…67,81,83 Both injections were examined in one study of high methodological and technical quality with 130 patients using four "control" groups. In this study 81 the proportion of patients with 50% or more pain relief was not significantly different among all comparison groups: 7% for transforaminal local anesthetic, 19% for transforaminal saline, 21% for intramuscular steroids, and 13% for intramuscular saline.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Description of epidural/intradiscal injection studies Summary of interventions Sixty-three studies evaluated the use of epidural/intradiscal injection for sciatica 95, (eight studies had more than two treatment arms 146,149,161,163,167,169,183,197 181,[183][184][185]187,193,194,197,200,202 (two studies had more than two treatment arms 183,197 ) compared different modes of administering epidural/intradiscal injections and 20 studies 149,167,[177][178][179][180]182,186,[188][189][190][191][192]195,196,198,199,203,204,207 compared the use of different epidural/intradiscal injections. Details of the interventions are summarised in Table 17b, but the findings of these studies are not considered any further here.…”
Section: Epidural/intradiscal Injectionmentioning
confidence: 99%
“…Most included epidural studies were RCTs (24/29, 83%); however, the proportion that were deemed good quality was very low (4/29, 14%), all of which compared epidural with inactive control. Although 10 studies 149,152,153,156,160,163,165,168,171,173 used and adequate method for generating a random number sequence, eight of these used sealed envelopes to conceal allocation, which is a partially adequate method. Only one study had good external validity.…”
Section: Summary Of Study Participants For Epidural/intradiscal Injecmentioning
confidence: 99%
“…Numerous authors have reported on their value in treating patients with radicular pain with the possibility of delaying or even obviating the need for lumbar discectomy in well-selected patients. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] There are two well-performed clinical studies in the peer reviewed literature that examined the crossover rates to surgery for patients who received either ESI or SNRB. In a prospective study, Buttermann et al found a crossover rate to surgery for patients with symptomatic disc herniations treated with ESI of 54% (27/50).…”
Section: Introductionmentioning
confidence: 99%